Nationalism Issues Found in the Bumi Manusia Movie - Khusnul Mei Anggraeni; Tarcisia Sri Suwarti; Festi Himatu Karima (Wawasan Pendidikan, 2023)
The problem of nationalism in the Bumi Manusia movie is analyzed in this final project. The purpose of this research is to identify Minke's character, to know the moral value of Minke's struggle, and to investigate the nationalist problem in Bumi Manusia movie. This study used a qualitative descriptive design. The main purpose of Vladimir Propp's theory of narrative analysis is to analyze data. The data were examined in five steps by the authors: watching the movie, understanding, identifying, discussing, and drawing conclusions based on the research findings. The results showed that: (1) there are 6 Minke characters, namely trustworthy, fair, caring, respectful, citizenship, and responsible; (2) found 8 moral values in the film, namely belief, responsibility, bravery, justice, critical-realistic, modesty, respect and caring; (3) the problem of nationalism contained in the film Bumi Manusia, namely Minke struggles to show Europeans that the Natives already had high dignity before they came, Minke and Nyai Ontosoroh fought for justice, he fought unfair European laws and demanded justice by writing several articles, one of which is " The European Law in view of the Native Law ", helping others with the principles of honesty and humanity and Javanese culture.